A relação dos valores de ângulo de fase com parâmetros de aptidão física e capacidade funcional e qualidade de vida em idosos - Silva, Alisson Alves (2018)
The phase angle is formed by the deviation of the electric current that is applied in the body, created from the moment that this current crosses the cellular membranes, being that part of these membranes will store energy, functioning like capacitors. The sample consisted of 37 elderly women, aged between 60 and 77 years. The objective of this study was to evaluate the phase angle as a predictor of functional capacity in the elderly. The elderly were divided into two groups: 19 elderly women exercising, water aerobics three times a week, and 18 elderly women who did not exercise at all. All of them underwent bioimpedance, anthropometry, hand hold tests, Time Up and Go and answered a quality of life questionnaire (SF-36). It has been found that the measured phase angle of this population is lower than the reference values for sex and for age, which is related to the strength abilities of palmar grip (right hand) and abdominal circumference.